PENGARUH CITA RASA DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN (SURVEI PADA PERUSAHAAN SMOOTH CHEESE TEA TASIKMALAYA) - Refian Kurnia Rustiawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2022)
One of the contemporary culinary ventures that are currently hits in Tasikmalaya is Smooth Cheese Tea which persists even though many contemporary drinks are popping up in Tasikmalaya. Smooth Cheese Tea always innovates in creating new products or flavors at very affordable prices so that they can survive until now and maintain customer satisfaction. This study aims to determine and analyze the effect of taste and price perception simultaneously and partially on consumer satisfaction surveys at the company Smooth Cheese Tea Tasikmalaya. The method used in this research is a quantitative and causal method with a survey approach. With a sample of 80 consumers of Smooth Cheese Tea. The data collected in the form of primary data. Data analysis in this study used multiple regression analysis, correlation coefficient and coefficient of determination using SPSS software. The results showed that taste and price perception simultaneously had a significant effect on consumer satisfaction. Partially, taste has a significant effect on consumer satisfaction. And also partially price perception has a significant effect on consumer satisfaction.